Carbon and nitrogen content to biovolume relationships for marine protist of the Rhizaria lineage (Radiolaria and Phaeodaria). Issue 5 (15th March 2021) - Mansour, Joost Samir; Norlin, Andreas; Llopis Monferrer, Natalia; L'Helguen, Stéphane; Not, Fabrice
Abstract: Rhizaria are large protistan cells that have been shown to be a major component of the planktic community in the oceans and contribute significantly to major biogeochemical cycles such as carbon or silicon. However, unlike for many other protists, limited data is available on rhizarian cellular carbon (C) and nitrogen (N) content and cell volume. Here we present novel C and N mass to volume equations and ratios for nine Rhizaria taxa belonging to Radiolaria (i.e., Collozoum, Sphaerozoum, Collosphaeridae, Acantharia, Nassellaria, and Spumellaria) and Phaeodaria (i.e., Aulacantha, Protocystis, and Challengeria ). The C and N content of collodarian cells was significantly correlated to cell volume as expressed by the mass : vol equations ng C cell −1 = −13.51 + 0.1524 × biovolume ( μ m 3 ) or ng N cell −1 = −4.33 + 0.0249 × biovolume ( μ m 3 ). Significant C and N content to volume correlations were also identified, and corresponding equations are proposed, for C : vol and N : vol of collodarian colonies (Radiolaria), and C : vol of the genus Protocystis (Phaeodaria). Furthermore, average C and N densities (mass per volume) are given for all studied Rhizaria. The densities and mass : vol equations established here could show that, with the exception of Aulacantha, biomass of most Rhizaria would have been underestimated using previously published generic protist C : vol ratios. We measured up to 35 times more C content for Acantharia than otherwise estimated, and between 1.4 and 21.5 times more for other taxa. Our mass : vol data will prove critical for model input and quantitative ecological studies of oceanic ecosystems.